Interrelationships between P-V-T and flow behavior of linear and nonlinear hydrocarbons - YAHŞİ, UĞUR (SOC PLASTICS ENG INC, 1998)
The aim of this work is to determine the branching effect on the flow behavior of alkanes. For this purpose, the zero-shear viscosity, eta(0), was analyzed in terms of the Simha-Somcynsky equation of state, SS-EOS, using the hole fraction, h = h(P, T) computed from it. For the analysis, eta(0)-data of the linear and three-branch alkanes measured in a wide range of temperature and pressure, were used. For the linear species, Utracki proposed a relation, viz. ln eta(0) = a(0)+a(1)/(h + a(2)), where a(1)= 0.79 and a(2) = 0.07 are the universal parameters for linear hydrocarbons and their mixtures. In this work, this relation was found to be valid for the linear but not for the branched alkanes.
Keywords: PRESSURE-DEPENDENCE; VISCOSITY; THERMODYNAMICS